Factor

\(ab^3 - a^3 b + bc^3 - b^3 c + ca^3 - c^3 a.\)

----------------Thanks!

madyl Apr 8, 2020

#1**+1 **

The way I would approach this is by factoring by grouping.

ab^3-a^3b= (ab)(b^2-a^2)

bc^3-b^3c= (bc)(c^2-b^2)

ca^3-c^3a= (ca)(a^2-c^2)

Using difference of squares...

ab^3-a^3b= (ab)(b^2-a^2)= (ab)(b+a)(b-a)

bc^3-b^3c= (bc)(c^2-b^2)= (bc)(c+b)(c-b)

ca^3-c^3a= (ca)(a^2-c^2)= (ca)(a+c)(a-c)

Putting the whole thing together, you get **(ab)(b+a)(b-a)+ (bc)(c+b)(c-b)+ (ca)(a+c)(a-c) which is completely factored**.

Hope it helps!

HELPMEEEEEEEEEEEEE Apr 8, 2020